2015
DOI: 10.1007/s10802-015-0086-8
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Patterns of Adverse Childhood Experiences and Current Symptoms and Impairment in Youth Referred For Trauma-Specific Services

Abstract: By the time children reach adolescence, most have experienced at least one type of severe adversity and many have been exposed to multiple types. However, whether patterns of adverse childhood experiences are consistent or change across developmental epochs in childhood is not known. Retrospective reports of adverse potentially traumatic childhood experiences in 3 distinct developmental epochs (early childhood, 0- to 5-years-old; middle childhood, 6- to 12-years-old; and adolescence, 13- to 18-years-old) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 47 publications
10
105
0
3
Order By: Relevance
“…These findings reflect the strong link between children’s exposure to IPV and disruptive behavior (Evans, Davies, & Dilillo, 2008), which some studies suggest may be mediated by harsh parenting (Grasso et al, 2015). Our harsh parenting class findings also highlight risk associated with harsh physical discipline, which was underlined in a recent meta-analysis providing evidence for an adverse effect of spanking on child outcomes, above and beyond physical abuse (Gershoff & Grogan-Kaylor, 2016).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These findings reflect the strong link between children’s exposure to IPV and disruptive behavior (Evans, Davies, & Dilillo, 2008), which some studies suggest may be mediated by harsh parenting (Grasso et al, 2015). Our harsh parenting class findings also highlight risk associated with harsh physical discipline, which was underlined in a recent meta-analysis providing evidence for an adverse effect of spanking on child outcomes, above and beyond physical abuse (Gershoff & Grogan-Kaylor, 2016).…”
Section: Discussionmentioning
confidence: 65%
“…In one study, polyvictimization was identified within developmental periods based on adolescents’ retrospective reports in a sample referred for trauma-specific services (Grasso et al, 2015). During the birth to 5-year period, polyvictimization was characterized by exposure linked to the caregiving environment.…”
mentioning
confidence: 99%
“…For example, adolescents may encounter a greater number and complexity of adversities compared to younger children (Grasso, Dierkhising, Branson, Ford, & Lee, 2016), and maternal distress can be highest during the middle school years, as mothers adjust to the many brain and hormonal changes that occur during adolescence and adjustments in the nature of the developmental relationship (Luthar & Ciciolla, 2016). Middle and high schools often are organized in ways that do not fit the developmental tasks or needs of adolescents, often de-emphasizing opportunities for ongoing, deep connections to adults and peers, healthy social networks, and opportunities to practice autonomous decision-making and higherlevel cognitive strategies, while emphasizing competition and social comparison (Eccles & Roeser, 2011).…”
Section: Adolescencementioning
confidence: 99%
“…Such events have been shown to impede or impair brain development, making children with violent histories and untreated symptoms related to traumatic events less able to practice emotional self-regulation and demonstrate impulse control than their peers without violence histories (Listenbee et al, 2012). Left unaddressed, these traumatic event exposures negatively impact youth throughout their lifetimes and may lead to substance use, suicide attempts, and other traumatic stress reactions that interfere with academic performance, important relationships in the youth's life, and ultimately can place youth at risk for continued and more severe justice involvement over time (Grasso, Dierkhising, Branson, Ford, & Lee, 2016;Ko et al, 2008). While past traumatic event exposure is not the only factor associated with delinquency, its prevalence among the justice-involved population has led some researchers to argue these factors must be considered in any juvenile justice hearing (Ford et al, 2006).…”
Section: Trauma and Youth Offendersmentioning
confidence: 99%